Bad Kitty : Puppy's big day - Bruel, Nick (Bruel, Nick. Bad Kitty., 2015)
Uncle Murray takes Puppy on a walk on a day that Bad Kitty is being unusually difficult, but has several unpleasant encounters with a police officer and one mean dog along the way. Text is interspersed with information about dog behavior, pet care, and more.